Moral Absolutes : Tradition, Revision, and Truth (Michael J. McGivney Lectures of the John Paul II Institute) - Finnis, John (Book collections on Project MUSE., 1991)
Moral Absolutes sets forth a vigorous but careful critique of much recent work in moral theology. It is illustrated with examples from the most controversial aspects of Christian moral doctrine, and a frank account is given of the roots of the upheaval in Roman Catholic moral theology in and after the 1960s.